Problemy i wyzwania muzealnictwa kościelnego w Polsce - Skrzydlewska, Beata (Archiwa, Biblioteki i Muzea Kościelne, 2015)
Religious museums, owned by different denominations, began to emerge in the first half of the nineteenth century. The museums of the Roman Catholic Church are the most numerous ones in this group. Regulations governing the activities of these institutions were included in the Code of Canon Law of 1918 and in the "Papal Directives concerning Church Art" of 1924. This issue was also regulated by a concordat of 1925 between the Republic of Poland and the Holy See. The latest directive is a circular letter of 2001 on Pastoral function of church museums. Nowadays, a number of religious museums have been created. An important issue is the permanent funding of museums. Another issue is the process of educating future priests in art history, or training church managers in the protection of cultural property. The outlined problems related to church museology indicate various tasks undertaken in this field - at every stage a different one. These tasks are closely connected with the targets set by the organizers and managers of cultural goods.